Exploring early interprofessional socialization: a pilot study of student’s experiences in medical history taking - Arnold, Christine; Berger, Sarah; Gronewold, Nadine; Schwabe, Denise; Götsch, Burkhard; Mahler, Cornelia; Schultz, Jobst-Hendrik (Journal of interprofessional care, 2020)
Traditional hierarchies and structures in healthcare, as well as traditional professional socialization practices, continue to create barriers to effective interprofessional collaboration. Nevertheless, some studies indicate that early socialization with other health professionals can build bridges and improve understanding of each other’s roles and contributions to patient care. This pilot study aimed to gain insights into the nursing and medical students’ experiences of interprofessional medical history taking during a collective learning activity. A descriptive case study was conducted using modified interviews based on the speed-dating (SD) technique to explore participants’ reasons for the choice of profession (SD1) and experiences of interprofessional history taking (SD2). Data were digitally captured using audio-recordings. An inductive-deductive approach to qualitative content analysis of transcribed responses was undertaken. Eighteen students (medicine n = 6; nursing n = 12) participated. Two main categories with sub-themes emerged from the inductive SD1 analysis: (a) reasons for choosing a career and (b) knowledge about professions. The SD2 deductive analysis identified three major categories with sub-themes: (a) breaking down barriers, (b) interprofessional role learning - interprofessional collaboration and (c) dual-identity development. Our findings showed that early interprofessional socialization of students supported their learning about the complementary roles of doctors and nurses and enabled them to gain early experiences of interprofessional teamwork.